ANALISIS POTENSI EKONOMI BERDASARKAN HISTORIOPRENEURSHIP DI DESA MASJID TUA SAMARINDA SEBERANG - Nurliyana, Nurliyana; Reza, Reza; Rahayu, Vitria Puri (Educational Studies: Conference Series, 2023)
This research aims to determine the potential for historiopreneurship-based businesses in the old mosque area of Samarinda city. This research was conducted as a descriptive research type with a qualitative approach, with information retrieval techniques using interviews and observation, the data was processed using qualitative analysis according to Miles and Huberman. The research results show that historiopreneurship-based potential is measured by three indicators, namely, type of business, environment and human resources. The results of the research show that people have poor independent financial management skills but already have an understanding so that financial management problems can be overcome, business owner sources are also able to carry out promotions and price competition due to threats from similar businesses. It can be concluded that there is economic potential based on historiopreneurship in the old mosque area.